POPULASI BEKANTAN (Nasalis larvatus) DI KAWASAN HUTAN MANGROVE SUNGAI SETINGGA ASIN DESA SEBUBUS KECAMATAN PALOH KABUPATEN SAMBAS - Puspitasari, Ayu Dewi; Erianto, Erianto; Rifanjani, Slamet (JURNAL HUTAN LESTARI, 2019)
Bekantan or Proboscis Monkey (Nasalis larvatus) is a herbivorous primate that occupies riparian areas, mangrove forests and coastal forests in Kalimantan. This species is an endemic primate on Kalimantan Island which has been declared as one of the protected species by the Government of Indonesia based on the Minister of Environment and Forestry Regulation number P.106 of 2018 concerning protected plant and animal species. Bekantan's main habitat in the form of mangrove swamp forest areas has now been opened due to human activities so that habitats suitable for the life of the proboscis monkey are reduced. This research was conducted in the mangrove forest of Sebubus Village, Paloh Subdistrict, Sambas Regency for 2 weeks effectively in the field to observe and count the number of Bekantan. Starting from September 16, 2018 until completion. This study aims to record the estimated population of Bekantan (Nasalis larvatus) in the mangrove forest area of Sungai Setingga Asin Sebubus Village, Paloh District, Sambas Regency. The research method used is the river survey method. Bekantan population calculation is done by the King method. Based on observations with 6 replications morning and evening. The area of the study area of 14.91 ha showed that there were 35.8 individuals and 1 group of proboscis monkey with a population density of 1.2 individual probes / ha and a group density of 0.03 groups / ha of proboscis.Keyword : mangrove forest Sebubus, proboscis monkey, river survey